2016
DOI: 10.3329/bjvm.v14i1.28820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kalo Jeera Seeds and Papaya Leaf Supplementation on the Performance of Broiler

Abstract: This experiment was conducted to determine the effect of papaya leaf (Carica papaya) and kalo jeera (Nigella sativa) seeds powdered supplementation in drinking water as a growth promoter in broiler chickens. A total of 20 Cobb-500 broiler chicks (day-old) were purchased from local hatchery (Nourish Poultry and Hatchery Ltd.) and after seven days of acclimatization chicks were randomly divided into two groups, A (n=10) and B (n=10). The group A was kept as a control and not treated. The group B was supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
4
11
1
Order By: Relevance
“…Mahejabin et al (2015) reported that neem, turmeric and papaya leaf extracts also increases TEC and hemoglobin concentration, which are in support of recorded data. Sorwar et al (2016) also reported that kalo zeera seeds and papaya leafs also increases the hemoglobin concentration, TEC and decreases ESR which were more or less similar to recorded study. Plant extracts and their fruits used as blood purifier, antioxidants and heptoprotective agents in the body (Bajaj and Tandon .24** ** = Significant at 1% (p<0.01) level of probability *= Significant at 5% (p<0.05) level of probability.…”
Section: Effects Of Probiotics and Phytoextracts On Hematological Parsupporting
confidence: 84%
“…Mahejabin et al (2015) reported that neem, turmeric and papaya leaf extracts also increases TEC and hemoglobin concentration, which are in support of recorded data. Sorwar et al (2016) also reported that kalo zeera seeds and papaya leafs also increases the hemoglobin concentration, TEC and decreases ESR which were more or less similar to recorded study. Plant extracts and their fruits used as blood purifier, antioxidants and heptoprotective agents in the body (Bajaj and Tandon .24** ** = Significant at 1% (p<0.01) level of probability *= Significant at 5% (p<0.05) level of probability.…”
Section: Effects Of Probiotics and Phytoextracts On Hematological Parsupporting
confidence: 84%
“…Microbial inhibition qualities of the incorporated papaya leave extracts into the chevon emulsion could be responsible. Antimicrobial properties of papaya leaves have already been documented by various scientists (Sorwar et al 2016;Miean and Mohamed 2001;Yogiraj et al 2014).…”
Section: Physico-chemical Quality Parametersmentioning
confidence: 90%
“…Carica papaya L. commonly known as ''Papaya'', family Caricaceae found in tropical regions like South Africa, Australia, Sri Lanka and India (Sorwar et al 2016). Papaya leaves, pulp and seeds also contain a variety of bioactive phyto-chemicals, including polyphenols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioactive ingredients are of emence importance because of their antioxidant and antimicrobial properties. The phenolic compounds present in plant sources showed potent importance in fresh, as well as in processed meat products in terms of extending storage life (Bhat et al, 2015a(Bhat et al, , 2015bSorwar et al, 2016;Kumar et al, 2015), improving functionality (Wagh et al, 2015;Wagh and Chatli, 2017) and reduced lipid oxidation (Jagtap et al, 2019;Joseph et al, 2014).…”
Section: Introductionmentioning
confidence: 99%